Análisis de tecnologías biométricas como método de seguridad informática aplicado a la implantación de un sistema informático para el cobro de aranceles de los programas de cuarto nivel del Instituto de Postgrado y Educación Continua de la ESPOCH. - Morocho Mónica, Remache Silvia (2016)
The research describes the comparative analysis of the most representative biometric technologies today such as: Recognition Fingerprint, Iris Recognition, Facial Recognition and Speech Recognition as a method of computer security analysis that will crystallize in the implementation of a system computer for charging tariffs fourth level programs Graduate Institute and Continuing Education ESPOCH. It is aimed to improve, facilitate and expedite the tasks performed by the Institute of Postgraduate Studies and Continuing Education (IPEC) and thus bridle students a more effective and efficient care by reducing the service time. One of the advances in technology since years ago it has been automating processes, despite the fact that automated want to say they are safe and now comes to getting a computer, safe and reliable system that protects data and information contained, commonly the security of a system of this kind has worked with id and passwords, which can be easily deciphered jeopardizing the system with hacker attacks or unauthorized access. It is for this reason that these parameters not considered sufficient to maintain a high level of security the implementation of a biometric technology as a method of computer security make it necessary. Therefore in this research it has included biometric technology based on fingerprint as security plug because they are unique for each user you characterize, and this technology is considered the most widely used because of its high reliability, security, and usability considering the low cost and convenience for end users. To implement the system installation has been necessary requirements: Netbeans 8.2, iReport, JasperReports, PostgreSQL Software biometric device and Hadware, hadware processor, RAM, a hard disk, printer, monitor, Biometric Device.